British Medical Journal. Supplement : A general medical service for the nation ([London : British Medical Association])
1938-04-30 1938 1930s 14 pages 262 APRIL 30, 1938 REPORT OF COUNCIL SUPPLEMENT TO THE BRITISH MEDICAL JOURNAL central council, representative of the voluntary hospitals of the country. The Commission suggests that while the central council would secure that no overlapping occurred between regional areas, the regional councils would, through a regional office, be responsible for the distribution of patients, the keeping of patients' records, the arrangement for the transfer of patients to and from hospitals, and the control of ambulance and other auxiliary services. It is hoped, further, that the organization of joint purchasing schemes, the giving of advice on new buildings and extensions, and the establishment of local funds on the lines of the King Edward's Fund for London would be amongst its duties. Such regional organizations linked by a central body would effect a substantial improvement in the present situation. 79. Although the Commission made the suggestion that representatives of local authorities should be invited to serve on regional councils, it is not to be expected that the adoption of the Commission's proposals on this subject would of itself result in the establishment of the necessary machinery for the other and extremely important form of co-operation, that between the local authority and the voluntary hospital authorities in its area. Between these agencies something more than the co-operation imposed by Section 13 of the Local Government Act, 1929, is required. A local authority can discharge its legal obligations under this section by consulting the voluntary hospital committee on the restricted subject of accommodation, and a voluntary hospital can be established or extended regardless of the statutory provision of the area. In some areas, where Section 13 committees have been set up, the consultation has been either rigid, limited and official, or completely absent. Co-operation is vital, but it would be unwise to rely merely on legal obligations. 80. What is wanted is the degree of consultation referred to by the Minister of Health in 1930: "It is the confident hope and expectation of the Minister that as procedure under Section 13 becomes established and regular, it may lead to wider arrangements for the fullest consultation between the local authority and the medical profession, not merely in regard to institutional accommodation and its use, but also in regard to those numerous developments in the health provision of the people which are implicit in the new organization laid down by the Act." 81. In those consultations all interests should be considered, including those of the general practitioner. In some areas local authorities will prefer to make substantial contributions to voluntary hospitals for the performance of certain work. In others they will prefer to make their provision direct. But in every case the needs of the area should be studied. No spirit of wasteful competition should appear between agencies concerned with one purpose — the provision of the necessary hospital accommodation for the area. 82. In some areas there are signs of a close and continuous co-operation. In others the fact that the boundaries of the natural hospital area are not coterminous with those of the local authority has militated against the establishment of an effective machinery of co-operation. While the rearrangement of local government boundaries to meet the situation is, for a number of reasons, hardly practicable, the creation of larger units of public health administration, by the removal of such functions from local authorities below a certain size, would make it possible to treat hospital services as well as the related medical services on a wider basis as regional problems. This subject is dealt with more fully in the section devoted to Administration (paras. 109-122). Until some such steps are taken, the problem of co-ordination between the two hospital agencies will prove difficult to solve. 83. Contributory schemes have aided to a remarkable extent the finances of voluntary hospitals, and it is possible to make arrangements whereby contributors are admitted to local authority as well as to voluntary hospitals, and payments from contributory schemes accepted by local authorities in lieu of direct assessment. Bearing in mind that the local authority must charge (and in Scotland may charge), it is clear that this provision not only makes financial co-operation between the local authority, the voluntary hospital, and the contributory scheme desirable, but emphasizes the need for separating contributory schemes from particular voluntary hospitals, and giving them reference to groups of hospitals over a wide area. 84. The Staffing of Hospitals. — Certain general principles underlie the Association's policy in this matter. When a hospital is devoting itself entirely to consultant and specialist work, only those practitioners who are equipped with the necessary knowledge and experience should undertake the responsibility for the medical work. On the other hand, where the conditions for which provision is made include those falling within the sphere and competence of the general practitioner, it is highly desirable that he should be freely admitted for the treatment of patients suffering from these conditions. In practice, the larger hospital devoting itself to specialist work is staffed by selected medical practitioners, while the smaller hospital to which the latter type of case is admitted is staffed on an unrestricted basis by general practitioners. Both kinds of hospital accommodation are necessary. There is, however, a growing need for a more extensive provision of a type of hospital or accommodation in which the general practitioner can treat cases falling within his sphere of competence. It commonly happens to-day that, for a social reason such as unsatisfactory home surroundings, a patient is admitted to hospital for a condition which in a more fortunately circumstanced patient would be treated at home by the patient's own doctor. It is contrary to the interest of the patient and damaging to the efficiency of general practice if social conditions lead to a discontinuity of medical treatment. 85. The importance to a general practitioner, and to the efficiency of his service to the community, of an association with hospital is difficult to exaggerate. The contacts it affords with fellow practitioners and the team work it involves stimulate him to a higher standard of efficiency, with consequent benefit to the community. 86. Further, in the case of those patients who are rightly transferred to the general wards of a hospital for specialist treatment unobtainable from the general practitioner, the transfer to hospital is often marked by an unnecessarily complete break between the patient and his family doctor. A much closer co-operation should be secured by more effective methods of communication and exchange of information between the hospital and the general practitioner. 87. Hospitals should, as a general rule, be staffed on a part-time basis — that is, by a visiting medical staff of practitioners who are also engaged in private practice. In this way the hospital benefits by the wider experience gained in hospital and private practice by members of its staff, and the general public, whether it seeks its consultant and specialist service at hospital or privately, can avail itself of the best service in the area. 88. Payment of Hospital Staffs. — Consideration of the change in clientele and of the change in the law leads inevitably to certain conclusions. The strictly charitable basis of the voluntary hospital now exists only to the extent that some of the poor are still treated gratuitously; the majority of persons obtaining treatment are those who can pay, desire to pay, and do in fact pay, directly or indirectly, towards their maintenance and treatment. Although the medical profession will gladly give, as always, its services gratuitously to those who cannot afford to pay for them, it is inequitable to require it to give its services without remuneration in voluntary hospitals which 292/847/1/60